The AGEB Algorithm for Solving Heat Equation in Two Space Dimensions and Its Parallelization on a Distributed Memory Machine - Alias, Norma; Sahimi, Mohamed Salleh; Abdullah, Abdul Rahman (Springer Verlag, Berlin, 2001)
In this paper, a computational analysis of parallelized a class of the AGE method based on the Brian variant (AGEB) is presented using (2 Ã— 2) blocks. The resulting schemes are found to be effective in reducing data storage accesses and communication time on a distributed computer system. All the parallel strategies were developed on a cluster of workstations based on Parallel Virtual Machine environment [6]. The experiments were run on the homogeneous cluster of 20 Intel Pentium IV PCs, each with a storage of 20GB and speed of 1.6Mhz. Finally, the results of some computational experiments and performance measurements will be discussed. In conclusion, the communication cost and computational complexity have effected the efficiency of the parallel strategies.